The quality of agriculture and food security policy processes at national level in Malawi: Results from the 2017/18 Malawi Agriculture and Food Security Policy Processes Endline Survey - Benson, Todd; Nyirenda, Zephania; Nankhuni, Flora; Maredia, Mywish K. (Michigan State University, 2018)
Over the past ten years, there have been several initiatives in Malawi to strengthen the processes through which the design and content of policies, strategies, and programs in the agriculture sector that affect the nation’s food security are established. In this report we present results of a study to assess the quality of these policy processes and the institutional framework through which they are conducted and how perceptions of their quality have changed over time. The study is based on a two-round survey of national stakeholders in Malawi on issues centered on agriculture or food security that was conducted in 2015 and 2017/18.